2007
DOI: 10.1007/s00705-007-1005-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual enteric and respiratory tropisms of winter dysentery bovine coronavirus in calves

Abstract: Although winter dysentery (WD), which is caused by the bovine coronavirus (BCoV) is characterized by the sudden onset of diarrhea in many adult cattle in a herd, the pathogenesis of the WD-BCoV is not completely understood. In this study, colostrum-deprived calves were experimentally infected with a Korean WD-BCoV strain and examined for viremia, enteric and nasal virus shedding as well as for viral antigen expression and virus-associated lesions in the small and large intestines and the upper and lower respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 33 publications
8
93
0
2
Order By: Relevance
“…Similar to other enteric viruses (Blutt & Conner, 2007; Park et al , 2007), SV-A RNA loads were detected in the sera of piglets orally inoculated with SV-A strain in this study, suggesting that SV-A might be able to penetrate the gut barrier from the luminal side through destruction of enterocytes in the villi. This result also implied that SV-A could reach other organs and tissues via cell-free transmission.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to other enteric viruses (Blutt & Conner, 2007; Park et al , 2007), SV-A RNA loads were detected in the sera of piglets orally inoculated with SV-A strain in this study, suggesting that SV-A might be able to penetrate the gut barrier from the luminal side through destruction of enterocytes in the villi. This result also implied that SV-A could reach other organs and tissues via cell-free transmission.…”
Section: Discussionsupporting
confidence: 72%
“…The distribution of SV-A antigens in tissues was evaluated by immunohistochemical examination using paraffin-embedded sections and an mAb against SV-A capsid protein as described previously (Park et al , 2007). Briefly, paraffin-embedded sections of each organ and tissue were deparaffinized and rehydrated through a graded series of alcohol in 0.1 M PBS and then treated with 0.1 % trypsin/0.1 % calcium chloride in PBS for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Antigenic and phylogenetic differences between isolates of BCoV from enteric and respiratory disease have been identified and the quasispecies structure of BCoV produces nucleotide sequence variation within a single isolate . However, in other cases, isolates of BoCV with >98% phylogenetic similarity have been identified in enteric and respiratory disease and an isolate of BCoV from a case of winter dysentery demonstrated both respiratory and enteric tropism after experimental infection . Phylogenetic differences between BCoV isolates from different geographical locations are greater than the differences between isolates from different clinical syndromes .…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the analysis of the S gene of South Korean isolates, where strains associated with dysentery clustered with a BRCoV isolate and were distant from the classic Mebus prototype, it was hypothesized that the same strain could cause both respiratory and enteric disease, and that BCoV had evolved to possess dual tropism (enteric and respiratory) (Park et al, 2006). To investigate this possibility, an experiment was performed with the South Korean winter dysentery strain KWD3, which showed that calves developed diarrhea without clinical manifestation of respiratory disease, whereas histopathology demonstrated mild to severe interstitial pneumonia caused by the KWD3 strain (Park et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, BCoV can simultaneously cause enteric and respiratory infections in the same animal (Park et al, 2007), although genetic markers for distinguishing between strains with both types of tropism were not identified during molecular analysis of the S glycoprotein (Kanno et al, 2007). Phylogenetic analyses based on the S-encoding gene sequence was performed in South Korea (Park et al, 2006), Japan (Kanno et al, 2007), and the USA (Fulton et al, 2013), which revealed that ancestral reference strains of BCoV that are exclusively associated with enteric manifestations clustered within a distinct phylogenetic group compared to the recent isolates associated with enteric and respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%